ANALYZING THE EFFECT OF SUCCESSION PLANNING AND LEADERSHIP DEVELOPMENT ON SUSTAINABLE ORGANIZATION PERFORMANCE: A STUDY OF IT-ENABLED SECTOR COMPANIES - Kulkarni, Sachidanand Ramrao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The world is moving towards an economy in which an organization’s knowledge is its most valuable asset (Al Khajeh, 2018). Therefore, it is necessary to continuously improve the professional skills and knowledge of the employees in order to complement the standardized competence that they require in order to complete their jobs. And achieving this requires quality leadership to trickle down from the top management. Numerous scholars investigate leadership styles in order to quantify the impact they have on employee performance, thus further affecting organizational performance as a whole (Cherian et al.,2020). Employee loyalty and motivation to work well will increase when leaders grant them autonomy, improving organizational productivity and producing better results in terms of organizational performance.